2010
DOI: 10.1007/s10067-010-1498-z
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate mofetil in systemic sclerosis-associated interstitial lung disease

Abstract: This study aimed to assess the effect of mofetil mycophenolate (MMF), an inhibitor of lymphocyte proliferation, on lung function and skin in patients with systemic sclerosis (SSc)-associated interstitial lung disease (SSc-ILD). In this retrospective study, we reviewed the medical files of 10 patients with SSc-ILD (eight females, 10 patients with diffuse SSc; mean age, 59.7 +/- 12.7 years; disease duration, 7.7 +/- 4.7 years). Patients were treated with MMF (2 g/day) for 12 months. Lung function tests and the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
5

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 13 publications
1
39
0
5
Order By: Relevance
“…To date, only observational studies on the efficacy of MMF have been performed. A recent meta-analysis, encompassing one prospective [54] and four retrospective studies [55][56][57][58], evaluated the safety and efficacy of MMF and mycophenolate sodium [59]. The results of this meta-analysis show that mycophenolate is a safe therapeutic agent and its administration has been linked with stabilisation of lung functional parameters.…”
Section: Nonselective Immunosuppressorsmentioning
confidence: 99%
“…To date, only observational studies on the efficacy of MMF have been performed. A recent meta-analysis, encompassing one prospective [54] and four retrospective studies [55][56][57][58], evaluated the safety and efficacy of MMF and mycophenolate sodium [59]. The results of this meta-analysis show that mycophenolate is a safe therapeutic agent and its administration has been linked with stabilisation of lung functional parameters.…”
Section: Nonselective Immunosuppressorsmentioning
confidence: 99%
“…In a prospective observational one year study of 14 patients who took MMF, 6 patients experienced at least a 10% improvement in their FVC and 5 patients' pulmonary function remained stable [50]. These small studies have had mixed results but, because observed improvements in FVC and DLCO have been documented [50][51][52], larger randomized trials are needed. This drug represents an attractive, less toxic possible alternative to cyclophosphamide.…”
Section: Mycophenolate Mofetilmentioning
confidence: 99%
“…Nevertheless, several reports from small case series describe a positive outcome in SSc-ILD patients treated with MMF, with stabilization or mild improvement of PFTs and HRCT fibrosis after 6 up to 24 months of therapy [84][85][86][87][88]. Stabilization of lung function has also been observed in a recent, uncontrolled, prospective study including early, immunosuppressive therapy-naive dcSSc patients, with a median treatment duration of 18 months [89].…”
Section: Mycophenolatementioning
confidence: 84%